PENGEMBANGAN MODUL AJAR BERBASIS BUDAYA JAWA MENGGUNAKAN MODEL RME UNTUK KEMAMPUAN BERFIKIR TINGKAT TINGGI (HOTS) PADA MATERI BANGUN DATAR DI KELAS IV SD NEGERI 107105 DESA KUTA BARU - Rita Dwi Yanti; Ahmad Landong; Putri syahpitri; Tasya Febriyanti; Ira Fauziah Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop a Javanese culture-based teaching module using the RME model for high-level thinking skills (hots) in flat building material in class IV of SD Negeri 107105, Kuta Baru village. Realistic Mathematics Education (RME) is a learning concept that presents material in the form of problems that must be solved by students based on understanding the concepts of students' daily lives. This research is development research or Research and Development (R&D) which is adapted from the ADDIE development model, with 5 development stages, namely: 1) Analysis (analisys); 2) Design (design); 3) Development (development); 4) Implementation; and 5) Evaluation. The subjects in this research were fourth grade students at SD Negeri 107105 New Kuta Village for the 2023/2024 academic year, while the objects in this research were teaching modules based on Javanese culture. The results of this research were that in trial I, classical completion of the results of students' high-level thinking abilities was 48% (14 students) and in trial II it was 90% (26 students). in trial II it was 90% (26 students). The average student response in trial I was 3.54 (Interested category) and in trial II was 3.64 (Interested category)